2007
DOI: 10.1002/ar.20585
|View full text |Cite
|
Sign up to set email alerts
|

Lobe Identity in the Mongolian Gerbil Prostatic Complex: A New Rodent Model for Prostate Study

Abstract: Knowledge of structural and physiological differences among the prostatic lobes (PL) is the basis for development of experimental studies in traditional laboratory rodents. Although Mongolian gerbil reproductive organs have been increasingly investigated, its prostate structure is far from being properly known, and investigations of this organ focused on the ventral lobe (VL). Thus, the present study provides a thorough morphological description of prostatic complex in the male adult gerbil on the basis of top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
48
0
18

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 35 publications
5
48
0
18
Order By: Relevance
“…This gerbil has proved to be a useful animal model for investigations of both the male prostate complex (Rochel et al, 2007) and female prostate (Santos et al, 2008). In the Mongolian gerbil, spermatogenesis begins at Week 2 of life and sexual maturity occurs at Week 10 (Ninomiya and Nakamura et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…This gerbil has proved to be a useful animal model for investigations of both the male prostate complex (Rochel et al, 2007) and female prostate (Santos et al, 2008). In the Mongolian gerbil, spermatogenesis begins at Week 2 of life and sexual maturity occurs at Week 10 (Ninomiya and Nakamura et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, hormonal variations on estrous cycle indicate peculiarities in the control of reproductive functions in gerbil (Fochi et al, 2008). Analysis of male prostatic complex in this specie revealed that the most voluminous component is the dorsolateral lobe whereas in rat and mouse is the ventral one (Rochel et al, 2007). Whereas some aspects of reproductive biology of gerbil have been well exploited in literature, others remain unknown, such as the ones concerning postnatal testicular development.…”
Section: Introductionmentioning
confidence: 97%
“…The Mongolian gerbil Meriones unguiculatus has been widely used in several areas of biomedical research (Cao et al, 2005;Ter-Mikaelian et al, 2007;Wiedemann et al, 2009) with an increasing interest on morphophysiology of genital system (Fochi et al, 2008;Rochel et al, 2007;dos Santos et al, 2003;Segatelli et al, 2004). The gerbil has been adopted in our laboratory as an excellent rodent model for studies on female prostate gland due the high incidence of this organ in comparison with other rodents (dos Santos et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, as análises iniciais indicavam que os lobos prostáticos do gerbilo apresentavam maior proximidade, sugerindo maior grau de semelhança com a próstata humana (8). Em adição, a análise dos tecidos associados à uretra de fêmeas revelou a existência de glân-dulas parauretrais (à semelhança das glândulas de Skene em humanos), que após estudos estruturais, bioquímicos e ultraestruturais nos levaram a concluir que se tratava de um complexo prostático feminino, mais volumoso em comparação com outros roedores de laboratório (9).…”
unclassified
“…Além disso, tal organização anatômica diferia da descrita para a maioria dos roedores, em que o LL também era observado. Visando a melhor entendimento da organização estrutural do complexo prostático do gerbilo e suas possíveis implicações funcionais, bem como a comparações com modelos clássicos de roedores para o estudo da próstata, realizou-se uma ampla descrição desse complexo (8). Para isso, além de se empregar os métodos morfológicos e ultraestruturais de alto padrão, foram implementados métodos de microdissecção, aliados à digestão enzimática.…”
unclassified